2015
DOI: 10.5897/ajmr2015.7451
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and enzyme activity of endophytic fungi isolated from Ocimum sanctum and Aloe vera

Abstract: The present study was carried out to isolate endophytic fungi from Ocimum sanctum and Aloe vera and to assess their antifungal activity against Rhizoctonia solani, Fusarium oxysporum, Colletotrichum falcatum and Helminthosporium maydis. The isolated fungi were further evaluated for production of extracellular enzymes such as amylase, cellulase, chitinase, pectinase, laccase, lipase and urease. During the study 18 endophytic fungi were isolated from leaves, stem and roots of O. sanctum and Aloe vera which are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…SaCS20." Endophytes use several multiple mechanisms to enable the uptake of nutrients in the edible portions of plants (113,114). Zn-solubilizing endophytes may be a better biofortifying agent to increase the Zn localization in the eatable portion of wheat (9,31), rice (108), and chickpea (16), thus presenting an alternative approach into the current strategies for biofortification.…”
Section: Endophytes: Who Is Inside the Plant For Micronutrient Biofortification?mentioning
confidence: 99%
“…SaCS20." Endophytes use several multiple mechanisms to enable the uptake of nutrients in the edible portions of plants (113,114). Zn-solubilizing endophytes may be a better biofortifying agent to increase the Zn localization in the eatable portion of wheat (9,31), rice (108), and chickpea (16), thus presenting an alternative approach into the current strategies for biofortification.…”
Section: Endophytes: Who Is Inside the Plant For Micronutrient Biofortification?mentioning
confidence: 99%
“…In addition, it was shown that both Bl1 and Ech4 isolates inhibited the B. cinerea mycelial growth by antibiosis, similar to other endophytic fungi; for example, fungi isolated from Theobroma cacao showed antibiosis against pathogens such as Moniliophthora roreri and Phytophthora palmivora [45], and endophytic fungi isolated from Aloe vera also inhibited by antibiosis the mycelial growth of Fusarium oxysporum [46]. The inhibition halo found in both isolates indicates that the antifungal activity of the obtained endophytic fungi is due to the secretion of diffusible secondary metabolites to the culture medium.…”
Section: Discussionmentioning
confidence: 87%
“…Fungal endophytes isolated from Ocimum sanctum were evaluated against Rhizoctonia solani, Fusarium oxysporum, Colletotrichum falcatum, and Helminthosporium maydis. A total of nine fungi were isolated, but none of them showed inhibition of mycelial growth (Yadav et al, 2015).…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%